Development of molecular breeding resources for increased pro-vitamin A carotenoids in sorghum grain - Cruet-Burgos, Clara María, author; Rhodes, Davina, advisor; Mason, Esten, committee member; Prenni, Jessica, committee member; Pressoir, Gael, committee member (Colorado State University. Libraries, 2022)
Vitamin A deficiency (VAD) affects millions of people in countries in Africa and South-East Asia, contributing to decreased immune response and increased morbidity and mortality from common infections. Sorghum [Sorghum bicolor L. (Moench)] is a staple cereal crop in these regions, thus, sorghum carotenoid biofortification is a potential method to improve the vitamin A status of these communities. The overall aim of this research was to determine the feasibility of biofortification breeding for sorghum grain carotenoids, and to develop genomic tools to assist in molecular breeding. Global sorghum germplasm collections were evaluated for pro-vitamin A carotenoids, and concentrations were found to be below target values. Due to the low number of accessions with above average pro-vitamin A content, the genetic diversity of the high carotenoid lines in the global germplasm was assessed. High carotenoid accessions were found to be highly related, hence, to increase genetic diversity for breeding, a genomic prediction model was used to identify additional germplasm with potentially high concentrations of pro-vitamin A carotenoids. Through a genome-wide association study, it was confirmed that carotenoid variation in sorghum grain is oligogenic, but there was also evidence of a polygenic component. Therefore both marker-assisted selection (MAS) and genomic selection (GS) may be effective in accelerating breeding efforts. KASP markers in linkage with genomic regions associated with carotenoid concentrations were developed and validated in six F2:3 populations. Two markers in the intronic region of the carotenoid pathway β-OH gene were identified as good candidates to use for MAS due to their predictive ability. A marker inside the coding sequence of the carotenoid pathway ZEP gene was also identified as a good marker for MAS. An RNA-seq experiment identified additional genes in the MEP, carotenoid biosynthesis and carotenoid degradation pathways that could be used for MAS. The results of these studies provide a foundation for vitamin A biofortification through genomics-assisted breeding.